THE GAP BETWEEN THEORY AND PRACTICE IN JOURNALISM EDUCATION: THE CASE STUDY OF THE DEPARTMENT OF MEDIA STUDIES IN NOVI SAD - Drašković, Brankica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
The paper considers the application of theoretical and practical skills of journalism education in the contemporary media environment that is mainly reduced to the market principles of infotainment. For quite some time the trend of tabloidization is shrinking the space for quality information and critical discussion about key topics of public interest, and additional problems arising more prominently in recent years are censorship and self-censorship. Media manipulation puts into question truthfulness and ethics of reporting, as well as the very role of a journalist as a corrective of social affairs and protector of public interest. This media situation largely undermines the approaches of journalism, thought in academic programmes, that treat journalism as a humanistic profession. Further, the development of communication technologies has brought new logics of media production and enabled distribution of content on various platforms. Following these observations and using in-depth interviews with the fiftheen graduates of journalism studies at the Department of Media Studies, Faculty of Philosophy in Novi Sad, the aim of this paper is to observe graduates’ attitudes based on their work experience in different Serbian media and to establish the level of applicability of journalism theory and technique gained at faculties, in the Serbian media practice. On the basis of analysis several recommendations are formulated: programmes should clearly respond to the demans of the contemporary media production and social flows, practical education should be enchanced by rising the technical capactities of faculties and reorganizing in-house media practice, teachers should have a role of co-travellers in gaining knowledge and skills and not of authoritative professors, they should have adeqaute professional and scientific competences for the courses they teach, the course in media literacy should be introduced, not only at faculties but also in the earlier stages of education.